Contextualization of Hijrah and Jihad for Religious Moderation of Religious Campus Students in Indonesia - Mahmudah, Siti; Alamsyah, Alamsyah; Anwar, Etin (Universitas Islam Negeri Raden Intan Lampung, 2022)
The meaning of hijrah and jihad has been misunderstood from spiritual meaning to plotical identity among millennial Muslims and students in Indonesia. They start from the desire to change one step to a better or Islamic life in more syar'i terms. However, in the end this understanding led to the emergence of radicalism and intolerance rather than a more contextual and moderate understanding that is relevant to be applied in the life of religion, nation and state. This study uses a qualitative method with the type of library research. The source of the data is obtained through various online media, journals and other literature, and the theory used as an analytical tool is the theory of contextualization. This study finds that the hijrah and jihad movements that are developing among millennials and students in Indonesia originate from a textual understanding of these meanings. The meaning of hijrah and jihad is only understood as a person's change from a bad life to a more syar'i in religion. This phenomenon must be immediately changed towards a textual understanding towards contextual and moderate by using a fast and precise strategy, starting from the teaching system of verses of the Koran and hadiths about Hijrah and Jihad in Higher Education which needs to be contextualized with the current era.